Evaluation of the Pulmonary Toxicity of a Fume Generated from a Nickel-, Copper-Based Electrode to be Used as a Substitute in Stainless Steel Welding - James M. Antonini; Melissa A. Badding; Terence G. Meighan; Michael Keane; Stephen S. Leonard; Jenny R. Roberts (SAGE Publishing, 2014)
Epidemiology has indicated a possible increase in lung cancer among stainless steel welders. Chromium (Cr) is a primary component of stainless steel welding fume. There is an initiative to develop alternative welding consumables [nickel (Ni)- and copper (Cu)-based alloys] that do not contain Cr. No study has been performed to evaluate the toxicity of fumes generated from Ni- and Cu-based consumables. Dose-response and time-course effects on lung toxicity of a Ni- and Cu-based welding fume (Ni-Cu WF) were examined using an in vivo and in vitro bioassay, and compared with two other well-characterized welding fumes. Even though only trace amounts of Cr were present, a persistent increase in lung injury and inflammation was observed for the Ni-Cu WF compared to the other fumes. The difference in response appears to be due to a direct cytotoxic effect by the Ni-Cu WF sample on lung macrophages as opposed to an elevated production of reactive oxygen species (ROS).